CLINICO-BACTERIOLOGICAL STUDIES ON PYODERMA IN GULBARGA REGION (KARNATAKA STATE) EMPHASES TO METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS - VIVEK KULKARNI; Y.M.JAYARAJ; C.T. SHIVANNAVAR; SAGAR M. ARALI; RAVI M (International Journal of Pharma and Bio Sciences, 2014)
Pyoderma is one of the commonest conditions encountered in dermatological practices. Emergence and spread of multidrug resistant pathogens are posing a great challenge. The present study was undertaken to investigate the common causative agents and their antibiotic susceptibility pattern in pyoderma. 173 pus samples were collected from the out patients of Department of Dermatology, Government hospital, Gulbarga, Karnataka (South India). Staphylococcus aureus was the main aetiological agent of pyoderma in 95 cases and was a sole aetiological agent in 53 cases (30.64%), while in association with Klebsiella it was in 42 cases (24.28%). Species of Coagulase negative Staphylococci, Streptococci, Klebsiella and Pseudomonas were isolated in12.42%, 7.84%, 5.88% and 3.27% of the cases respectively. Among the 95 strains of Staphylococcus aureus isolated, 37 (38.95%) were Methicillin resistant (MRSA) and 13(13.68%) were Vancomycin resistant (VRSA). Thus emergence of drug resistance is becoming a threat and needs monitoring.